1990
DOI: 10.1051/jphys:0199000510220257100
|View full text |Cite
|
Sign up to set email alerts
|

Growth of two dimensional domains in copolymer thin films

Abstract: Quenching experiments on very thin films (≃ 1 000 Å) of symmetric diblock copolymer deposited on solid substrates result in the formation of circular relief domains at the free surface of the sample. It is due to the quantization of the possible thicknesses of the sample which accompanies the lamellar ordering of the two species parallel to the substrate. Depending on the average thickness of the film, the domains can be depressions or elevations. Based on the conjecture of a simple dislocation structure of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 5 publications
8
41
0
Order By: Relevance
“…If higher magnification micrographs are acquired along a constant g s track, the familiar progression from smooth surface to islands to co-continuous to holes back to a smooth surface as a function of h is found. [3,4,[19][20][21] Likewise, if a series of micrographs are obtained from a constant h path, the morphology is observed to change from symmetric to antisymmetric with the nature of the surface patterns formed depending on h. [14] An example of this morphology change is shown in Figure 3 where AFM images of an M ¼ 51k block copolymer film acquired at h % 71 nm (2.37 L o ) are presented. The images were obtained in tapping mode and have a common height scale (full range 50 nm) where the brighter color indicates tall features and the dark color indicates holes on the film surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If higher magnification micrographs are acquired along a constant g s track, the familiar progression from smooth surface to islands to co-continuous to holes back to a smooth surface as a function of h is found. [3,4,[19][20][21] Likewise, if a series of micrographs are obtained from a constant h path, the morphology is observed to change from symmetric to antisymmetric with the nature of the surface patterns formed depending on h. [14] An example of this morphology change is shown in Figure 3 where AFM images of an M ¼ 51k block copolymer film acquired at h % 71 nm (2.37 L o ) are presented. The images were obtained in tapping mode and have a common height scale (full range 50 nm) where the brighter color indicates tall features and the dark color indicates holes on the film surface.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that when these polymers are cast as thin films, a preferential surface interaction between one of the blocks and the substrate causes the lamellae to become oriented parallel to the substrate. [2,[17][18][19][20][21][22] These films are smooth when the film thickness (h) is an integral multiple of the lamella thickness (L o ) but have an incomplete surface lamella that forms islands or holes of L o when the thickness deviates from this value. [2][3][4] In addition to film thickness, the substrate surface energy (g s ) may affect the morphology of the thin film.…”
Section: Introductionmentioning
confidence: 99%
“…A step edge between the L ν ∥ and L ν+2 ∥ phases will typically involve ν continuous monolayers plus one semi-infinite bilayer as depicted schematically in Figure 1. Ausserréet al 5 initially argued that the bilayer should exist one monolayer below the air surface, rather than on top as in Figure 1. Furthermore, they suggested that the lateral width of the step should be comparable to the bilayer thickness, L 0 , but AFM measurements by Maaloum et al 13 found the steps to be much broader.…”
mentioning
confidence: 99%
“…The appearance of hole and island patterns as a function of the film thickness is a well-known phenomenon. [33,34] However, optical and microscopic investigations of thickness gradients of polystyrene/poly-(methyl methacrylate) (PS/PMMA) film libraries revealed additionally spinodal morphologies and broad smooth regions ( Figure 10). [35,36] …”
Section: Block Polymer Ordering Behavior and Phase Behaviormentioning
confidence: 99%